Abraham Heschel and the Catholic Heart - O'Hare, Padraic (Studies in Christian-Jewish Relations, 2011)
This essay associates the deep abiding influence of Rabbi Heschel on Christians with his unique expression of an incarnational religious imagination, appealing to all Christians with a “Catholic heart.” In this view, the opposing worldview to dualism, life is experienced sacramentally, God is experienced immanently and religious symbols are experienced as deeply efficacious. The essay focuses especially on the incarnational trait of associating mystical experience and contemplative prayer with prophetic action and reveals how this link is nurtured and cultivated by Heschel and by his friend, Thomas Merton.